Analysis of BRImo Application User Satisfaction Through The End User Computing Satisfaction Model in Kolaka District - Muhamad Stiadi; Jimsan Jimsan; Mardianto Mardianto (Universitas Alma Ata, 2024)
The objective of this study is to assess the degree of user satisfaction with the BRImo application within the Kolaka district. The research method used is quantitative descriptive which aims to describe the characteristics of each research variable which is sourced from primary data and then processed by calculating the percentage of user satisfaction. Research results using The End User Computing Satisfaction (EUCS) model show that the content variable has a satisfaction value of 85%, accuracy of 81%, form of 85%, ease of use of 85%, and timeliness of 83%. In general, users are satisfied with these variables.